1999
DOI: 10.1103/physrevlett.83.4089
|View full text |Cite
|
Sign up to set email alerts
|

High Real-Space Resolution Measurement of the Local Structure ofGa1xInxAsUsi

Abstract: High real-space resolution atomic pair distribution functions (PDF)s from the alloy series Ga1−xInxAs have been obtained using high-energy x-ray diffraction. The first peak in the PDF is resolved as a doublet due to the presence of two nearest neighbor bond lengths, Ga-As and In-As, as previously observed using XAFS. The widths of nearest, and higher, neighbor pairs are analyzed by separating the strain broadening from the thermal motion. The strain broadening is five times larger for distant atomic neighbors … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
108
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 17 publications
13
108
0
Order By: Relevance
“…Local-structure PDF studies of the supposed solid solutions (In,Ga)As, Zn(Se,Te), and (Li,Na)AsSe 2 have shown that materials with single-phase Bragg diffraction patterns can exhibit nanoscale clustering of the end members that is evidenced by split nearest-neighbor bond distances in the PDF. [30][31][32] For extensive nanoclustering of Sb and As we would see short bonds corresponding to As-As (2.52Å), plus long Sb-Sb bonds (2.91Å). The low-r region of the (Color online) Least-squares refinements to the SbAs PDF collected at room temperature using (a,b) x-rays and (c) neutrons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Local-structure PDF studies of the supposed solid solutions (In,Ga)As, Zn(Se,Te), and (Li,Na)AsSe 2 have shown that materials with single-phase Bragg diffraction patterns can exhibit nanoscale clustering of the end members that is evidenced by split nearest-neighbor bond distances in the PDF. [30][31][32] For extensive nanoclustering of Sb and As we would see short bonds corresponding to As-As (2.52Å), plus long Sb-Sb bonds (2.91Å). The low-r region of the (Color online) Least-squares refinements to the SbAs PDF collected at room temperature using (a,b) x-rays and (c) neutrons.…”
Section: Resultsmentioning
confidence: 99%
“…The PDFs do not show any short As-As distances which would signal the onset of nanoscale phase separation that is invisible to Bragg diffraction. [30][31][32][33] Hightemperature Bragg diffraction finds the atomic mixing to become disordered above 550 K. Unlike GeTe, the compound SbAs does not become cubic upon heating.…”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
“…Extra positional disorder, manifested by enlarged temperature factors, has been found on both metal and As sites as well. Both the static displacement and the positional disorder have been found to peak at a composition x = 0.5 [6,7].…”
Section: A Local A[omic Vtructure Of In /G[latremiconductor mentioning
confidence: 99%
“…More experimental details can be found in refs. [6,7]. Experimental reduced structure factors and the corresponding atomic PDFs G(r) are shown in Figs.…”
Section: A Local A[omic Vtructure Of In /G[latremiconductor mentioning
confidence: 99%
“…However, peaks at higher-r region exhibit significant broadening ( Figure 5(b)) indicating that there is some structural relaxations taking place as bond-bending distortions, as has been observed before in semiconductor alloys. [80,81] This homogeneous strain increases rapidly for the ultra-small (CdSe_QD1) nanoparticles revealing that they have a significant compressive strain. Comparable behaviour is also seen with increases in the PDF peak broadening with decreasing nanoparticle size indicating that the inhomogeneous strain, or width of the bond-length distribution in the nanoparticles, also increases.…”
Section: Lattice Strain In Nanoparticlesmentioning
confidence: 99%